Biosecurity and insecurity: the interaction between policy and ritual during the foot and mouth crisis - Nerlich, Brigitte; Wright, Nick (White Horse Press, 2006)
In 2001 a highly infectious animal disease, foot and mouth disease, broke out in the UK and spread rapidly. In May, when the spread seemed to be slowing down, new disease hotspots appeared in previously little affected regions, such as North Yorkshire. New biosecurity rules were imposed. Based on a series of semi-structured interviews with stakeholders, this article shows that the biosecurity measures farmers implemented during the epidemic meant more than just reducing the risk of spreading FMD. For many, cleansing and disinfecting became Foot and Mouth. Biosecurity actions became invested with symbolic values and, in particular, were ritualised as part of the symbolic spatial construction of an otherwise 'invisible' enemy.